The Secret of Marriage Fortune: Between Madura Tradition and Islamic Education in West Kalimantan - Sofyan, Anas; Hermansyah; Sapendi (PT. Hafasy Dwi Nawasena, 2025)
This research reveals the secret behind the tradition of getting married on days and months that are considered good by the Madurese people in West Kalimantan, specifically in Sungai Kunyit Hulu Village, Mempawah Regency. In Madurese culture, choosing the right time to get married is not only based on practical considerations, but also beliefs about luck and prosperity in the future. This research methodology uses a qualitative approach with in-depth interview methods and participant observation to understand the meaning and beliefs behind this tradition. The research results show that choosing a good day and month for a wedding is the result of a combination of religious figures, cultural heritage and life experiences. This tradition not only serves as a guide for couples getting married, but also strengthens social ties within the Madurese community in Sungai Kunyit Hulu Village. These findings provide insight into how traditional beliefs continue to play an important role in the lives of modern society, as well as demonstrate the Madurese community's efforts to maintain their cultural identity amidst globalization.